PENGARUH PROFITABILITAS, ARUS KAS OPERASI, DAN ARUS KAS BEBAS TERHADAP DIVIDEN KAS PADA PERUSAHAAN MANUFAKTUR TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2005 - 2009 - Emmi Suryani Nasution (Jurnal Akuntansi Muhammadiyah (JAM), 2011)
The purpose of this study is to examine the effect of profitability, operating cash flow, and free cash flow on cash dividend of manufacturing companies listed at the Indonesia Stock Exchange in the period 2005-2009.            The population in this study are 15 listed companies from the  manufacturing sector in Indonesia Stock Exchange which have the profitability, positive operating cash flow, positive free cash flow, and pay cash dividends. The time horizon used is a combination of cross-sectional with longitudinal (time series). The study population consists of 15 issuers with 75 observations. This study uses census methods. To examine the influence of profitability, operating cash flow, and free cash flow to cash dividends use multiple linear regression models.            The results show that (1) profitability, operating cash flow, and free cash flow simultaneously influence on the cash dividends on listed companies from the manufacturing sector at the Indonesia Stock Exchange during the 2005-2009 period. (2) Affect the profitability of cash dividends on companies from the manufacturing sector listed at the Indonesia Stock Exchange during the 2005-2009 period. (3) Operating cash flow has influence to cash dividends at companies manufacturing sector listed at the Indonesia Stock Exchange during the 2005-2009 period. (4) Free cash flow have negative influence to the cash dividend at companies manufacturing sector listed at the Indonesia Stock Exchange during the 2005-2009 period. Keywords: Profitability, Operating Cash Flow, Free Cash Flow, Cash Dividends.